Дети блокады: повесть / Михаил Сухачев - Сухачев Михаил Павлович (Школьная библиотека, 2018)
Экземпляры: ДБ (20200831) / Инвентарный номер: 52726 / Цена: 220.60 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С 91 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44